ANALYSIS OF THE INFLUENCE OF THE FINANCIAL SERVICES AND INSURANCE, REAL ESTATE, MANUFACTURING AND TRADE SECTORS ON ECONOMIC GROWTH IN SOUTH TANGERANG - Maisa Reresimi; Viniyati Maftuchach; Jumadi Jumadi; Santi Santi (Jurnal Ekonomi, 2023)
This study aims to analyze the impact of the Financial Services and Insurance, Real Estate, Manufacturing, and Trade sectors on economic growth in South Tangerang. Annual economic data comes from the Central Statistics Agency, which is interpolated into monthly data with Eviews 12. The interpolated data is then processed using the Ordinary Least Square method. The statistical analysis results show that all sectors have a positive and significant impact on the city's economic growth. The Financial Services and Insurance Sectors show that easier access to financing and financial stability contribute to sustainable economic growth. The Real Estate sector has proven to have a positive impact on infrastructure and property developments that encourage new jobs and business growth. The Manufacturing Sector significantly impacts by creating jobs and increasing added value in production. The trade sector plays an important role in linking supply and demand and increasing business activity and consumption. The F statistic test also shows that together, these four sectors have a significant impact on South Tangerang's economic growth. This study concludes that developing and strengthening the Financial Services and Insurance, Real Estate, Manufacturing, and Trade sectors can effectively spur sustainable economic growth in South Tangerang. The trade sector plays an important role in linking supply and demand and increasing business activity and consumption. The F statistic test also shows that together, these four sectors have a significant impact on South Tangerang's economic growth. This study concludes that developing and strengthening the Financial Services and Insurance, Real Estate, Manufacturing, and Trade sectors can effectively spur sustainable economic growth in South Tangerang. The trade sector plays an important role in linking supply and demand and increasing business activity and consumption. The F statistic test also shows that together, these four sectors have a significant impact on South Tangerang's economic growth. This study concludes that developing and strengthening the Financial Services and Insurance, Real Estate, Manufacturing, and Trade sectors can effectively spur sustainable economic growth in South Tangerang.